MANAGEMENT OF KARST AQUIFERS IN SERBIA FOR WATER SUPPLY - Stevanović Z.; Jemcov I.; Milanović S. (My University, 2007)
Karst aquifers represent one of the main sources of water supply in Serbia. Wide distributions of karstic areas, abundant reserves, and excellent quality of karst groundwater have been the reasons for its extensive use in water supply systems throughout the country. In Serbia, 70 karstic sources have been tapped for centralized water supply, with the assessed minimal capacity exceeding 4.5 m3/s. Most of the large cities of Eastern and Western Serbia currently use karst groundwater for water supply; however, due to unstable flow regime when only natural springflow is tapped, numerous problems arise during the recession period (summer–autumn). During the last two decades, after favorable conditions had been confirmed through hydrogeological survey and feasibility studies, several newly constructed systems for artificial control of karst aquifers (mostly in Eastern Serbia) resulted in significantly improved water supply.
Keywords: KARST AQUIFER; REGIME CONTROL; WATER SUPPLY; SERBIA